STATISTICAL PARAMETERS ANALYSIS OF SEDIMENT GRAIN SIZE FROM RAYA RIVER BENGKAYANG REGENCY, WEST BORNEO - Muhardi Muhardi; Yusuf Arief Nurrahman; Risko Risko; Muliadi Muliadi; Kanti Rahayu; Heni Susiati (Marine Geological Institute of Indonesia, 2021)
The study of the statistical analysis parameters of grain size in the waters of Sungai Raya was carried out in order to understand the characteristic of the sediment in the river and coastal areas. The grain size by sieving method, and analyze the statistical parameters including the average grain size, sorting, skewness, and kurtosis. Sediment samples were acquired from six stations with each station consisting of three sampling points representing river west bank, river midstream, river east bank, and the coastal area consisting of five stations. The results of the sediment analyses showed that the average grain size in the river ranges from 1.23 to 2.77 mm, and on the beach area is between 1,52 - 2,59 mm, classified as fine sand, medium sand, very fine sand, and coarse sand with predominant fine sand in all stations. The results of the statistical parameter analysis of the grain size of the bottom sediment in the waters of Sungai Raya exhibit the average diameter value ranging from 1.23 to 2.77 mm, classified as fine sand to medium sand. This value indicates that the type of sediment in this location is dominated by silt with grain sizes ranging from < 0.05 - 0.002 mm. The sorting value ranges from 0.14 to 1.59 mm, categorized into moderately sorted, moderately well-sorted, very well sorted, and poorly sorted classes. The average value of skewness is 2.17 with the classification of the bed load being very fine and kurtosis value ranges from 0.72 to 1.67 indicates the classification in these waters is platycuric, mesokurtic, leptokurtic, and very leptokurtic. These finding concluded that in the study area there is a variation in the angularity of the sediment grains due to the different hydrodynamic processes